1993
DOI: 10.2307/1941800
|View full text |Cite
|
Sign up to set email alerts
|

Maximization of Aboveground Grassland Production: The Role of Defoliation Frequency, Intensity, and History

Abstract: Production of tallgrass prairie vegetation was measured on experimental plots in which defoliation intensity and frequency were manipulated by mowing and using movable exclosures on areas chronically grazed by cattle. Defoliation history largely controlled whether or not defoliated plants overcompensated (exhibited enhanced production compared to undefoliated controls) for tissue removal. Plants on chronically grazed sites only compensated for foliage removed by grazers. Production on plots mowed prior to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
118
4
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(141 citation statements)
references
References 40 publications
17
118
4
2
Order By: Relevance
“…3a), and it also increases the operation cost of haymaking. This result is different from that obtained in temperate grasslands under more humid environments, where more herbage production is normally expected under multiple than single harvests in each year (Turner et al 1993). The result in the present experiment probably means that the rate of growth of the herbage after mowing in mid June is similar to that of the plots that had not been harvested at this time.…”
Section: Herbage Production and Mowing Frequencycontrasting
confidence: 99%
“…3a), and it also increases the operation cost of haymaking. This result is different from that obtained in temperate grasslands under more humid environments, where more herbage production is normally expected under multiple than single harvests in each year (Turner et al 1993). The result in the present experiment probably means that the rate of growth of the herbage after mowing in mid June is similar to that of the plots that had not been harvested at this time.…”
Section: Herbage Production and Mowing Frequencycontrasting
confidence: 99%
“…In fact, immediately following defoliation, grasses usually experience a stoppage in root growth that reflects the percentage of foliage removed and continues until recovery of the top growth is advanced (Crider, 1955). For example, in most C 3 and C 4 grasses, root growth ceases immediately following a ≥ 50% leaf area removal (Richards, 1993;Turner et al, 1993). For shorter cutting-heights and/or harvest frequencies, therefore, reduction in respective root and crown biomass is expected, an observation also made in the current study.…”
Section: Belowground Biomasssupporting
confidence: 73%
“…For shorter cutting-heights and/or harvest frequencies, therefore, reduction in respective root and crown biomass is expected, an observation also made in the current study. This is so because of preferential resource allocation to aboveground growth at the expense of roots, a scenario usually exhibited by plants recovering from defoliation (Richards, 1984;Turner et al, 1993;Turner et al, 2007).…”
Section: Belowground Biomassmentioning
confidence: 99%
“…Other studies have reported that moderate grazing could cause an increase in ANPP by overcompensation (Turner et al, 1993;Zou et al, 2014), and the photoassimilate partitioned to the root and soil (Hafner et al, 2012;Zou et al, 2014). In the future, when implementing and managing GfGP grassland, factors that could improve ANPP and belowground C allocation, including the selection of suitable grass with higher ANPP and belowground C allocation (Zhao et al, 2015), and the reasonable intensity of grazing, should be considered.…”
Section: Predicted Restoration Time Of Soil C Stock and Improvements mentioning
confidence: 99%